2005
DOI: 10.1016/j.neuron.2005.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Development of Long-Term Dendritic Spine Stability in Diverse Regions of Cerebral Cortex

Abstract: Synapse formation and elimination occur throughout life, but the magnitude of such changes at distinct developmental stages remains unclear. Using transgenic mice overexpressing yellow fluorescent protein and transcranial two-photon microscopy, we repeatedly imaged dendritic spines on the apical dendrites of layer 5 pyramidal neurons. In young adolescent mice (1-month-old), 13%-20% of spines were eliminated and 5%-8% formed over 2 weeks in barrel, motor, and frontal cortices, indicating a cortical-wide spine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

55
611
1
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 631 publications
(672 citation statements)
references
References 32 publications
55
611
1
5
Order By: Relevance
“…They also showed that in adult barrel cortex, Ͼ70% of spines are persistent over an 18-month interval, underscoring the remarkable stability of dendritic spines in adulthood and their potential role in long-term information storage. 34 A recent study examining spine dynamics in the visual, somatosensory, and auditory cortices in ϳ2 month-old mice found that Ͼ80% of spines are stable over 3 weeks, 35 in agreement with the view that adult spines are largely stable.…”
Section: Imaging Synaptic Structural Plasticity In the Young And Adulsupporting
confidence: 54%
See 3 more Smart Citations
“…They also showed that in adult barrel cortex, Ͼ70% of spines are persistent over an 18-month interval, underscoring the remarkable stability of dendritic spines in adulthood and their potential role in long-term information storage. 34 A recent study examining spine dynamics in the visual, somatosensory, and auditory cortices in ϳ2 month-old mice found that Ͼ80% of spines are stable over 3 weeks, 35 in agreement with the view that adult spines are largely stable.…”
Section: Imaging Synaptic Structural Plasticity In the Young And Adulsupporting
confidence: 54%
“…Although this newer study showed the majority of adult spines can be stable over weeks, more than 20% of total spines in 6-months-old mice are still considered transient and persist less than 4 days. 33 On the other hand, Zuo et al 34 showed that in adults (Ͼ 4 months old), spines exhibited similar low rates of elimination and formation in barrel, primary motor, and frontal cortices as their previously reported low turnover rates in the primary visual cortex. They also showed that in adult barrel cortex, Ͼ70% of spines are persistent over an 18-month interval, underscoring the remarkable stability of dendritic spines in adulthood and their potential role in long-term information storage.…”
Section: Imaging Synaptic Structural Plasticity In the Young And Adulmentioning
confidence: 52%
See 2 more Smart Citations
“…Multiple studies have used repeated imaging in the brain to document changes in dendritic spines in the neocortex (Konur and Yuste, 2004;Zuo et al, 2005). Both studies show that while spines are continually eliminated throughout early postnatal life, spines become more stable as the animal matures.…”
Section: Analysis Of Postnatal Nervous System Development In Mice Usimentioning
confidence: 99%